(untitled) (Sebha University Conference Proceedings, 2025)
Hybrid electric vehicles (HEVs) play a crucial role in the development of sustainable transportation solutions by integrating several power sources. This study centers on a novel modelling system that drives a synchronous motor with permanent magnet (PMSM) in the context of hybrid electric vehicles (HEVs) utilizing solar (PV) panels, batteries, fuel cells, and super capacitors. The objective of integrating these diverse energy storage technologies is to enhance vehicle efficiency and optimize energy management. The FC, or fuel cell, is utilized alongside the PV panels to ensure uninterrupted power generation throughout the day. Batteries and super capacitors serve as energy storage devices to regulate power fluctuations and provide rapid energy surges during acceleration. The PMSM motor is renowned for its exceptional efficiency and torque characteristics, making it seamlessly integrate into the vehicle’s drive train. This study evaluates the overall viability, energy efficiency, and dynamic performance of the hybrid power system using comprehensive simulations. Examining crucial elements such as energy conversion efficiency, charging/discharging methodologies, and system integration challenges is necessary to assess if the system can meet HEV performance standards. The results demonstrate the potential of the hybrid PV/FC/battery/SC-powered PMSM motor system to enhance vehicle range, reduce emissions, and promote eco-friendly transportation alternatives in MATLAB Simulink. This study enhances the progress of next-generation hybrid electric vehicles by employing improved power management techniques and renewable energy sources.